2012
DOI: 10.1016/j.jevs.2012.08.097
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of host adaptation in Lawsonia intracellularis infections

Abstract: Background: Lawsonia intracellularis is the causative agent of proliferative enteropathy, an endemic disease in pigs and an emerging concern in horses. Enterocyte hyperplasia is a common lesion in every case but there are differences regarding clinical and pathological presentations among affected species. We hypothesize that host susceptibility to L. intracellularis infection depends on the species of origin of the bacterial isolate. The objective of this study was to evaluate the susceptibilities of pigs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Reported clinical signs and macro-and microscopic findings, all consistent with the literature (Lester 2001, Pusterla et al 2010, Vannucci et al 2012) associated with positive immune staining for Lawsonia intracellularis allowed us to reach the diagnosis of equine proliferative enteropathy (EPE). Unlike pigs, in which lesions and immunostaining are more highly concentrated in the final third of the small intestine, in horses, these lesions can also be found in the duodenum, as reported in this case.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Reported clinical signs and macro-and microscopic findings, all consistent with the literature (Lester 2001, Pusterla et al 2010, Vannucci et al 2012) associated with positive immune staining for Lawsonia intracellularis allowed us to reach the diagnosis of equine proliferative enteropathy (EPE). Unlike pigs, in which lesions and immunostaining are more highly concentrated in the final third of the small intestine, in horses, these lesions can also be found in the duodenum, as reported in this case.…”
Section: Discussionsupporting
confidence: 75%
“…Al-Ghamdi et al (2012) reproduced proliferative enteropathy (EP) in 2-month-old foals using a pure culture of L. intracellularis and intestinal mucosa homogenates obtained from experimentally infected pigs. However, Vannucci et al (2012) did not observe the same results, as pigs infected with equine isolated and foals infected with L. intracellularis isolated from pigs showed no clinical signs, decline in performance, pathological changes or hypoproteinemia, suggesting adaptation to the host.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Guedes and Gebhart (2003c), using monoclonal antibodies (MAbs 2001 and IG4 MAbs) and one polyclonal antibody (1999 PABs) for L. intracellularis, demonstrated through Western blot analysis that all L. intracellularis isolates, except one strain from a hamster, showed reactivity for all antibodies; which may indicate some difference in outer membrane proteins of the hamster isolate. Vanucci et al (2012) demonstrated evidences of host adaptation in L. intracellularis infections in swine and horses. In their study strong lesions and clinical signs were observed when the animals were challenged with an inoculum species specific.…”
Section: Discussionmentioning
confidence: 95%